Economic-environmental equilibrium-based bi-level dispatch strategy towards integrated electricity and natural gas systems. (1st January 2021) - Song, Xiaoling; Wang, Yudong; Zhang, Zhe; Shen, Charles; Peña-Mora, Feniosky
Abstract: Even though economic dispatch of integrated electricity and natural gas systems using optimization techniques has been widely conducted, a cooperative distributed and multi-objective optimization is still needed for meeting multi-energy demands from both conventional and renewable energy resources. In this study, an original bi-level economic-environmental equilibrium model is proposed to optimize a dispatch strategy for an integrated system, which include combined cooling, heating, and power and power to gas technologies. By optimizing cooperative distributed decisions, the system attempts to provide heat/cooling, power and natural gas loads. An equilibrium consideration of economic energy supply and environmental carbon emission control is achieved using a multi-objective optimization in the model. To reflect interactions of individual system operators in a cooperative distributed manner, a bi-level optimization is applied to address the respective decisions and objective functions. Subsequently, an interactive solution approach based on Non-dominated Sorting Genetic Algorithm-II and genetic algorithm is specifically designed to solve the model by updating individual decisions interactively and iteratively, and the optimality of an integrated solution lies in the capability to coordinate two system operators for a reliable, economic and environmental energy supply. Performance of the dispatch strategy is validated for a case with various system configurations. The obtained results showed that multi-energy needs are met, economic-environmental trade-offs achieved and hierarchical interactions addressed. Proper managerial suggestions are also provided based on comparison analyses. The proposed method is therefore worthy of being popularized in integrated systems. Graphical abstract: Highlights: A cooperative way to propose a multi-objective bi-level dispatch model. Electric power, natural gas and heat/cooling supplies are interacted in two levels. An interactive solution method is designed based on the model. Performance comparisons are made to propose corresponding managerial recommendations.